Two- and Three-Dimensional Transesophageal Echocardiography for Two Separate Primary Cardiac Lymphomas in the Right Heart. (July 2017) - Kuroda, Masataka; Sakamoto, Takashi; Orihara, Masaki; Saito, Shigeru
Abstract : Supplemental Digital Content is available in the text.Published ahead of print January 23, 2017.